2013
DOI: 10.1186/1746-4269-9-18
|View full text |Cite
|
Sign up to set email alerts
|

A cross sectional survey of knowledge, attitude and practices related to house flies among dairy farmers in Punjab, Pakistan

Abstract: A cross sectional survey of knowledge, attitude and practices related to house flies among dairy farmers in Punjab, Pakistan AbstractBackground: House flies are of major public health concerns in areas with poor sanitation and hygienic conditions. Unfortunately, sanitation and hygiene have always been ignored in dairy farms particularly in the developing or low-income countries. Management of these flies mostly depends on the awareness regarding associated hazards and protective measures taken by the people t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 19 publications
1
34
0
2
Order By: Relevance
“…The interest manifested toward knowledge by the respondents is a promising factor for early improvement of practices of animal husbandry and milk processing; this general interest acts as a factor for reducing exposure, not only to Brucella spp, but also to other zoonotic pathogens. The current study found that the level of education was an important predictor and was positively associated with the adoption of preventive practices: this correlation was observed in many KAPs surveys (Xiang et al, 2010;Holt et al, 2011;Khan et al, 2013;Lindahl et al, 2015). This study can help to develop appropriate policies of preventive measures by improving the knowledge and practice of farmers in sanitation, hygiene and waste management.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The interest manifested toward knowledge by the respondents is a promising factor for early improvement of practices of animal husbandry and milk processing; this general interest acts as a factor for reducing exposure, not only to Brucella spp, but also to other zoonotic pathogens. The current study found that the level of education was an important predictor and was positively associated with the adoption of preventive practices: this correlation was observed in many KAPs surveys (Xiang et al, 2010;Holt et al, 2011;Khan et al, 2013;Lindahl et al, 2015). This study can help to develop appropriate policies of preventive measures by improving the knowledge and practice of farmers in sanitation, hygiene and waste management.…”
Section: Resultsmentioning
confidence: 91%
“…Practice generally depends on knowledge, economic stability and the socio-economic condition of farmers. The poor knowledge about brucellosis and the natives' population is interfering in Brucellosis' control and its spread (WHO, 2009;Addo et al, 2011;USAID, 2011;Khan et al, 2013). In Palestine, since 1998 the Ministry of Agriculture in cooperation with the UNDP/PAPP organization started the implementation of the Brucellosis Control Program, financially supported by Argentina, Japan and Spain, and technically by the WHO, FAO and OIE organizations.…”
Section: Resultsmentioning
confidence: 99%
“…Avoiding excessive organophosphate and pyrethroid use on crops grown around dairies would also enhance resistance management in house flies. This might be of particular importance since most of the dairy producers in Punjab have been reported (Khan et al 2013b) to be linked with crop farming and they often used leftover insecticides sporadically for the management of flies and other dairy pests. Moreover, lack of cross-resistance between deltamethrin and spinosad provides an opportunity to use these products in rotation for the management of resistance, and house flies in the field.…”
Section: Discussionmentioning
confidence: 98%
“…Musca domestica (Diptera: Muscidae) constitutes a worldwide problem whenever poor sanitation and bad hygienic conditions exists (Khan et al 2013). It is considered as one of the leading insects causing environmental health problems as it always accompanies human daily activities whether indoors or outdoors.…”
Section: Introductionmentioning
confidence: 99%